Peran Guru Paud Dalam Mengoptimalkan Perkembangan Belajar Anak Melalui Media Pembelajaran Berbasis Visualisasi Di Paud KB Agape Desa Iraono Lase - Asnita Gulo; Syifa Fauziah (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
Learning in early childhood requires strategies that align with their developmental characteristics, especially because children find it easier to understand information thru concrete experiences and visual stimuli. However, the application of visual media in early childhood education (ECE) still faces several limitations, making the role of teachers a crucial factor in supporting the optimization of children's learning development. This study aims to describe the role of early childhood education (ECE) teachers, the impact of using visualization-based learning media, and the challenges that arise in its implementation at PAUD KB Agape, Iraono Lase Village. This research uses a qualitative approach with a case study method. The research subjects include the school principal, classroom teachers, and supporting teachers. Data were obtained thru observation, interviews, and documentation, then analyzed thru the stages of data reduction, data presentation, and conclusion drawing.The research results show that teachers play roles as planners, facilitators, motivators, directors, and evaluators in utilizing visual media. The media used includes picture cards, posters, illustrated storybooks, short videos, and illustrated worksheets. The use of visual media has a positive impact on children's cognitive, language, learning motivation, and socio-emotional development. The obstacles encountered include limited facilities, teachers' limited ability to develop media, time constraints, and differences in children's characteristics. The conclusion of the research emphasizes that visualization media effectively supports children's learning development if teachers can manage the learning process creatively and tailor it to the children's needs. Therefore, schools are advised to enhance facility support, while teachers need to continue developing simple yet innovative variations of visual media.